2023
DOI: 10.1097/aln.0000000000004851
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam Dosing for Gastroscopy: A Randomized Noninferiority Trial

Huichen Zhu,
Zhongxue Su,
Hongmei Zhou
et al.

Abstract: Background Remimazolam, an ultra-short-acting benzodiazepine, may provide adequate sedation for endoscopy while causing less cardiovascular or respiratory disturbance than propofol. Although fixed-dose administration is suggested, body weight affects the volume of the central chamber and thus affects the sedation depth that can be achieved by the first dose. We aimed to compare the efficacy and safety of different doses of remimazolam and propofol by body weight for sedation during gastroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Some studies, such as those conducted by Chen et al [ 18 ], Zhang et al [ 55 ], Cao et al [ 56 ], and Xiao et al [ 57 ], reported faster recovery times in the Remimazolam compared to Propofol group. However, other studies, such as those conducted by Hu et al [ 51 ], Dong et al [ 58 ], and Zhu et al [ 59 ] reported longer recovery times in the Remimazolam compared to the Propofol cohort. One study by Guo et al [ 39 ] found no significant difference in recovery times between the two sedatives for GI endoscopy, particularly in elderly patients.…”
Section: Comparison Of Efficacy and Cost Of Remimazolam To Other Seda...mentioning
confidence: 89%
See 2 more Smart Citations
“…Some studies, such as those conducted by Chen et al [ 18 ], Zhang et al [ 55 ], Cao et al [ 56 ], and Xiao et al [ 57 ], reported faster recovery times in the Remimazolam compared to Propofol group. However, other studies, such as those conducted by Hu et al [ 51 ], Dong et al [ 58 ], and Zhu et al [ 59 ] reported longer recovery times in the Remimazolam compared to the Propofol cohort. One study by Guo et al [ 39 ] found no significant difference in recovery times between the two sedatives for GI endoscopy, particularly in elderly patients.…”
Section: Comparison Of Efficacy and Cost Of Remimazolam To Other Seda...mentioning
confidence: 89%
“…In the upper and lower GI endoscopic procedures, Remimazolam has shown excellent efficacy. In the RCT by Zhu et al [ 59 ], it was established that 0.2 mg/kg dose of Remimazolam provided adequate and non-inferior sedation as compared to propofol (1.5 mg/kg) in upper GI endoscopy with a superior safety profile. Furthermore, Ye et al [ 80 ] also noted that the ED95 of 0.2039 mg/kg (95%CI 0.1753-0.3896) for Remimazolam was consistent with previous published literature.…”
Section: Remimazolam In Upper Lower and Pancreaticobiliary Endoscopymentioning
confidence: 99%
See 1 more Smart Citation